Sting Nematode Belonolaimus longicaudatus Rau (Nematoda: Tylenchida: Belonolaimidae) - William T. Crow (EDIS, 2015)
Among the most destructive plant-parasitic nematodes to a wide range of plants, Belonolaimus longicaudatus damages plant roots. When the plants cannot take up water and nutrients from the soil, they become stunted, wilt, and with severe infestation, die. Florida is considered to be the point-of-origin for Belonolaimus longicaudatus, and therefore this nematode exhibits a great deal of diversity in morphology, host preference, and genetics in our region. This 6-page fact sheet was written by W. T. Crow, and published by the UF Department of Entomology and Nematology, March 2015. (Photo W. T. Crow, UF/IFAS)